People’s Participation in Panchayatiraj Institutionof Rural West Bengal - Pal, Tapas Kumar (International Journal of Psychosocial Rehabilitation, 2012)
Rural India’s transition to decentralization is expected to have a substantial societal impact, as it provides a three-tier form of local self-government, the Panchayati raj: at the village, district, and Panchayat Block levels. In Bengal, the state of eastern India, after the administration of the Left Front came into power, there are traces of far-reaching societal transformation, particularly in view of revitalizing a Panchayat system of three levels. In the earliest years of Left Front administration, the village of Sabha, the general voting body spanning 10 to 12 villages and the Gram Sansad, a forum for local democracy at the ward levels, eagerly attended Panchayat meetings and participated in decision-making at the village council level. Today, however, there are very few persons involved in programmes funded by the government. There are few Panchayat meetings attended, with some classes and sectors of the community nearly always excluded. To tackle that issue, the Western Bengal government has recently tried and established Gram Unnayan Samiti (GUS) or Village Development Councils, consisting of political members of the elect and opposition parties, as well as certain nominated members, for a further delegation of power and responsibilities to the local government. The CIS should contribute more to grassroots engagement. In this research, we examine the formal policies of decentralisation and people‟s involvement in Western Bengal and analyse the dynamics of political decision-making processes on an operational level following CIS implementation. We have analysed the audio recordings of Gram Sabhas meetings and the dynamics of the newly established CIS to discover how often people are actually taking part. We propose that solutions lay in a strong third-level to deal with questions of lack of openness and accountability in decision-making and recommend how to do so.